2011
DOI: 10.1111/j.1601-0825.2011.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical stress on cytokine production in mandible‐derived osteoblasts

Abstract: These results suggest that MDOB play a role in cytokine production in response to mechanical stress and that occlusal force may support the maintenance of mandible bone homeostasis by activating bone remodeling through osteoclastogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
(65 reference statements)
2
19
0
Order By: Relevance
“…A tensile strain upregulated OPG expression of mouse osteoblastic MC3T3-E1 cells and downregulated RANKL expression. Moreover, hydrostatic pressure changed the ratio of RANKL/OPG in favor of RANKL both at the mRNA and protein levels in a magnitude-and time-dependent manner (13). These studies all demonstrated that mechanical stress suppressed osteoclastogenesis and inhibited bone resorption.…”
Section: Discussionmentioning
confidence: 73%
“…A tensile strain upregulated OPG expression of mouse osteoblastic MC3T3-E1 cells and downregulated RANKL expression. Moreover, hydrostatic pressure changed the ratio of RANKL/OPG in favor of RANKL both at the mRNA and protein levels in a magnitude-and time-dependent manner (13). These studies all demonstrated that mechanical stress suppressed osteoclastogenesis and inhibited bone resorption.…”
Section: Discussionmentioning
confidence: 73%
“…These previous results suggest that mandible-derived osteoblasts play an important role in inflammatory cytokine production in response to mechanical stress and mechanical stress may regulate the homeostasis of mandible bone by activating bone remodelling through osteoclastogenesis in vivo [16]. Therefore, occlusal force may be a key regulator of regeneration of periodontal tissue, including the alveolar bone and PDL.…”
Section: Discussionmentioning
confidence: 84%
“…Our group has previously reported that mechanical stress increased the inflammatory cytokines production in a magnitude-and time-dependent manner and changed the ratio of receptor activator of nuclear factor kappa-B Odontology ligand/Osteoprotegerin (RANKL/OPG) in favour of RANKL in mandible-derived osteoblasts [16]. These previous results suggest that mandible-derived osteoblasts play an important role in inflammatory cytokine production in response to mechanical stress and mechanical stress may regulate the homeostasis of mandible bone by activating bone remodelling through osteoclastogenesis in vivo [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations